Implementation of Problem Based Learning (PBL) Learning Model Integrated with Culturally Responsive Teaching (CRT) to Increase Motivation to Learn Mathematics - Nurhalizah, Siti; Sagala, Pehulysa; Nasution, Amanda Syahri; Panjaitan, Dedy Juliandri; Zebua, Mesra Belinda (Universitas Muhammadiyah Sumatera Utara (UMSU), 2025)
This study was conducted to improve the quality of learning in the classroom, low motivation in Mathematics subjects in class X DKV 1 SMK Negeri 10 Medan. Through observation that students have low learning motivation. Learning that is carried out continuously without innovation makes the level of student motivation low, with this study the researcher combines the Problem Based Learning (PBL) learning model with the Culturally Responsive Teaching (CRT) approach. This type of research is classroom action research which is carried out in 2 cycles. The subjects of the study were 33 students. The data taken were in the form of observations and questionnaires. The results of the study showed that there was an increase in student learning motivation of 19% which was obtained through a motivation questionnaire based on student learning motivation indicators. Significant results can be seen from the percentage obtained during cycle I which was only 61%, while in cycle II it was 80%. This shows that the implementation of the Problem Based Learning (PBL) model integrated with Culturally Responsive Teaching (CRT) can increase students' motivation to learn mathematics so that learning becomes more innovative and enjoyable.Keyword: Learning Model, PBL, CRT, Motivation, Mathematics